2007
DOI: 10.3136/nskkk.54.379
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cholesterol-Lowering Effects of Soymilk and Okara Treated by Lactic Acid Fermentation in Rats

Abstract: We investigated the e#ect of lactic acid-fermented soymilk, in which a portion of soymilk was replaced with okara, on plasma and liver lipid concentrations in rats. Male Sprague-Dawley rats were fed a high-cholesterol diet (control diet) or test diet in which ,*῍ of the diets were replaced by soymilk, fermented soymilk or a fermented soymilk/okara mixture. Fermented soymilk/ okara was expected to be smoother in taste because finely powdered okara was used, instead of intact soybeans. Only rats fed a fermented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…However, the hepatic cholesterol content of the rats that ingested soy yogurt was not significantly suppressed as compared with the CO group (Table 4). In our previous studies, hepatic cholesterol contents fell in rats fed a high-cholesterol diet 16) and a cholesterol-free diet with ingestion of SY. 17) However, in the present experiment, the level of hepatic cholesterol in the rats fed soy yogurt showed only a tendency towards decrease (p < 0:01 vs. control).…”
Section: Hepatic Lipids Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the hepatic cholesterol content of the rats that ingested soy yogurt was not significantly suppressed as compared with the CO group (Table 4). In our previous studies, hepatic cholesterol contents fell in rats fed a high-cholesterol diet 16) and a cholesterol-free diet with ingestion of SY. 17) However, in the present experiment, the level of hepatic cholesterol in the rats fed soy yogurt showed only a tendency towards decrease (p < 0:01 vs. control).…”
Section: Hepatic Lipids Profilesmentioning
confidence: 99%
“…DNA microarray analysis indicated that soy yogurt ingestion downregulated lipogenesis and cholesterol synthesis, and up-regulated -oxidation of fatty acid and cholesterol catabolism. Suppression by soy yogurt of hepatic lipids in rats fed a high-cholesterol diet 16) and a cholesterolfree diet 17) depended on the regulation of synthesis and degradation of lipids.…”
Section: Dna Microarray Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared soymilk fermented with lactic acid bacteria of vegetable origin in order to ingest it more easily. We have previously reported that fermented soymilk reduced the plasma and hepatic cholesterol concentrations in rats fed on a high-cholesterol diet 13) and that more than a 10% of soy protein in the diet was necessary to achieve a significant physiological effect on rats fed with a cholesterol-free diet by ingesting fermented soymilk. 14) Fermented soymilk prepared by using bifidobavterium breve YIT 4065 has been reported to improve the lipid metabolism.…”
mentioning
confidence: 99%
“…We examined the beneficial use of okara supplemented in lactic acid-fermented soymilk (soy yogurt). We already investigated the effects of soy yogurt on plasma and hepatic lipid profiles in rats (Kitawaki et al, 2007) and found that soy yogurt exhibits lipidmetabolism modification (Kitawaki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%